Potential of Beneng Taro (Xanthosoma undipes) Fructooligosaccharides (FOS) in Enhancing Total Count of Lactic Acid Bacteria in Synbiotic Yogurt - Septariawulan Kusumasari; Tubagus Bahtiar Rusbana; Sri Mulyati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Synbiotic dairy products combine probiotics and prebiotics to deliver synergistic health benefits, including improved gut microbiota modulation, immune support, and enhanced functional quality. Fructooligosaccharides (FOS) are recognized prebiotic compounds that selectively promote the growth of lactic acid bacteria (LAB), strengthening the probiotic effect. However, commercial FOS sources such as chicory and Jerusalem artichoke remain costly and largely imported, limiting access for small-scale food producers in developing regions. This study aimed to evaluate the potential of Beneng taro (Xanthosoma undipes K. Koch), an underutilized Indonesian tuber, as a local FOS source to enhance LAB viability in synbiotic yogurt. FOS were extracted via enzymatic hydrolysis and incorporated into milk at 1–3% (w/v). LAB counts, pH, and sensory characteristics were evaluated. The 2% FOS addition significantly increased LAB viability (8.46 ± 0.02 log CFU/mL) compared to control (7.86 ± 0.05 log CFU/mL) (p < 0.05). Furthermore, the FOS-enriched yogurt demonstrated improved texture, reduced syneresis, and enhanced consumer acceptability. These findings highlight Beneng taro as a promising, sustainable source of prebiotic carbohydrates that can contribute to Indonesia’s bioresource valorization and local circular food economy.